Efficacy of combined gonadotropin-releasing hormone analogue and growth hormone therapy in girls with central precocious puberty: a systematic review and meta-analysis - Jin, Sufeng; Sun, Yanhong; Zhu, Zhouyue; Yu, Haitao (Frontiers in Endocrinology, 2025)
BackgroundCentral precocious puberty (CPP) in girls is characterized by premature activation of the hypothalamic-pituitary-gonadal axis, often leading to early epiphyseal closure and compromised adult height. While gonadotropin-releasing hormone analogues (GnRHa) are the standard therapy to suppress puberty and preserve height potential, the benefit of adding growth hormone (GH) to improve height outcomes remains unclear. This work aims to evaluate the efficacy of combined GnRHa and GH therapy compared to GnRHa monotherapy in improving growth outcomes in girls with CPP.MethodsA systematic search of PubMed, Embase, Web of Science, and Cochrane Library was conducted up to May 2025. Eligible studies comparing GnRHa + GH combination therapy to GnRHa monotherapy in girls with CPP were included. Primary outcomes included final height and final height minus target height (FH–TH). Secondary outcomes included predicted adult height (PAH), height gain, height change during treatment, growth velocity, and bone maturation (ΔBA/ΔCA). Pooled weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated using fixed- or random-effects models based on heterogeneity. Subgroup analyses were conducted by study design.ResultsNine studies were included. Combination therapy significantly improved FH–TH (WMD = 1.01 cm, 95% CI: 0.28 to 1.73; P = 0.006), PAH (WMD = 4.27 cm, 95% CI: 3.47 to 5.08; P < 0.0001), height gain (WMD = 3.45 cm, 95% CI: 1.73 to 5.17; P < 0.0001), height change during treatment (WMD = 3.31 cm, 95% CI: 1.76 to 4.86; P < 0.0001), and growth velocity (WMD = 1.40 cm/year, 95% CI: 0.90 to 1.91; P < 0.0001), with no significant effect on bone maturation (ΔBA/ΔCA) (WMD = 0.01, 95% CI: –0.05 to 0.07; P = 0.77). No significant improvement in final height was observed (WMD = 0.14 cm, 95% CI: –1.66 to 1.94; P = 0.88).ConclusionGH supplementation during GnRHa treatment in girls with CPP enhances short-term growth outcomes without accelerating bone age but does not consistently improve final adult height. Combination therapy may be considered for selected patients with poor growth prognosis; however, further high-quality randomized trials are needed to refine patient selection and optimize treatment strategies.